Factors in malignant transformation of ovarian endometriosis: A narrative review - Andrea Giannini; Francesca Massimello; Marta Caretto; Giulia Cosimi; Paolo Mannella; Stefano Luisi; Angiolo Gadducci; Tommaso Simoncini (Taylor & Francis Group, 2024)
Endometriosis is a common estrogen-dependent inflammatory disease with a chronic course and a tendency to recur. The association between endometriosis and cancer has been studied for several years. Numerous reports have demonstrated a strong association between specific ovarian malignancies and endometriotic lesions. Atypical endometriosis has been widely described as a malignant precursor to ovarian epithelial tumors, particularly clear cell carcinomas and endometrioid carcinomas. These histological types associated with endometriosis develop predominantly in the ovary rather than in extragonadal sites. The detailed molecular mechanism of etiology remains unclear. Recent studies have analyzed the genetic and molecular mechanisms involved in endometriosis-associated ovarian cancer. A critical role appears to be played by a carcinogenic model based on iron-induced oxidative stress, which is typical of the endometriosis microenvironment. It has been hypothesized that trans-tubal reflux of blood, endometrial cells and associated iron-induced oxidative stress underlie the development of endometriosis-associated ovarian cancer. However, the multifactorial mechanisms of this malignant transformation are not fully understood. The aim of this review is to summaries the current epidemiological, histopathological, genetic and molecular findings in the progression of endometriosis-associated ovarian cancer.